2016
DOI: 10.15376/biores.11.2.5312-5321
|View full text |Cite
|
Sign up to set email alerts
|

Visual Grading and Structural Properties Assessment of Large Cross-Section Pinus radiata D. Don Timber

Abstract: The use of large cross-section timber for structural purposes has increased in Spain, and knowledge of its properties is strategically necessary. The Spanish visual strength-grading standard UNE 56544 (2011) efficiency applied to large cross-section structural timber was analyzed using a sample of 363 specimens of radiata pine (Pinus radiata D. Don.) from the Basque Country and Catalonia, Spain. Different sizes were tested (80 × 120 × 2400 mm ). Bending strength, modulus of elasticity, and density were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…However, rejection by twist parameter was really high for Scots, Salzmann and maritime pine (from 44% to 80%) and low only for radiata pine (8%). A broader study of the visual grading and mechanical properties of radiata pine revealed that twist is the key singularity for the visual grading yield, mainly in small cross-sections (7). This is in agreement with current results where twist was the key singularity but large cross-section radiata pine were the less affected specimens.…”
Section: Comparison Between Wet and Dry Gradingsupporting
confidence: 91%
See 1 more Smart Citation
“…However, rejection by twist parameter was really high for Scots, Salzmann and maritime pine (from 44% to 80%) and low only for radiata pine (8%). A broader study of the visual grading and mechanical properties of radiata pine revealed that twist is the key singularity for the visual grading yield, mainly in small cross-sections (7). This is in agreement with current results where twist was the key singularity but large cross-section radiata pine were the less affected specimens.…”
Section: Comparison Between Wet and Dry Gradingsupporting
confidence: 91%
“…Stapel and van-de-Kuilen (6) reported that rejected pieces from Norway spruce at thicknesses of 100 mm or more fulfilled the required values of mechanical properties for S10 grade. Hermoso et al (7) found same result on radiata pine at thicknesses of 200 mm using UNE 56544. Moya et al (8) applied the idea of a cross-section limit in their proposed non-European visual grading standard for a specific 50x150 mm 2 cross-section.…”
Section: Introductionmentioning
confidence: 53%
“…They were graded, following a previously published categorization system [35], with boards being designated as either: (i) “EC7”, which corresponds to strength class C14 [13], or (ii) “Reject” for structural purposes. Since knots are the main singularities that usually define the bending strength of softwood timber beams [35,36], these rejected boards were then re-graded according to a proposed new structural grade designated “CTH” (coniferous thinning), which permitted surface knots with a maximum diameter of up to 4/5 of the height of the board ( h ), and an edge knot diameter equal to the board’s width ( b ). The study sample of the present work comprised 11% of timber graded as EC7 and 89% as CTH.…”
Section: Methodsmentioning
confidence: 99%
“…Due to changes in forest management and improved genetic material, rotation periods have been reduced as growth rates have increased. However, as a result of this, the trees have a different proportions of anatomical and wood structures deriving into a significant reduction in their mechanical properties (Dowse and Wessels 2013, Wessels et al 2014, Hermoso et al 2016. As these problems arose, there have been several researches carried out on wood quality, related to wood density and MFA (micro fibril angle) being the two most influential properties for predicting mechanical properties (Tsoumis 2009, Burdon et al 2001, Auty et al 2014, Moore et al 2015, Mäkinen and Hynynen 2012.…”
Section: Introductionmentioning
confidence: 99%